Development of a car ownership model in Metro Manila - Rubite, Caesar P.; Tiglao, Noriel Christopher C.
The Metro Manila region has been continuously growing swiftly over the past years. This rapid urbanization in the city center has spilled over its periphery, the adjoining municipalities. Accessibility between the outer periphery and the city center becomes very critical especially when people seek employment within the city center. With the lack of efficient transit system on one hand, and improved socioeconomic characteristics of the household on the other, the demand for private cars is expected to increase also. However, the limited supply of road space cannot keep pace with increasing demand. Therefore, it is necessary to manage the growth of car ownership in metropolitan areas. A basic understanding of individual and household attitudes towards car ownership would enable the formulation of effective policies and plans for managing car ownership. Knowledge of car ownership paves the way for a better understanding of the people's behavior which will greatly affect policy formulation and analysis in the future. The research is concerned with determining the various household characteristics which influence the household's decision to own a car. This decision is modeled as a binary choice incorporating the different household and individual characteristics as explanatory variables. The study used data taken from Metro Manila Urban Transportation Integration Study Home Interview Survey (HIS) database. The research revealed that the major factors affecting household decision to own a car are household income and number of working adults.
Keywords: Car ownership model; Transportation engineering